2010
DOI: 10.5589/m10-020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of new spaceborne SAR sensors for sea-ice monitoring in the Baltic Sea

Abstract: Abstract. In this study, synthetic aperture radar (SAR) data from the Advanced Land Observing Satellite (ALOS) and the Envisat, RADARSAT-2, and TerraSAR-X satellites were compared to evaluate their usefulness for sea-ice monitoring in the Baltic Sea. Radar signature characteristics at different frequencies, polarizations, and spatial resolutions are presented for three examples from 2009. C-band like-polarization data, which have been used for operational sea-ice mapping since the early 1990s, serve as a refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…While most of the work carried out in the past was concerned with C-band data; confer, e.g., [7]- [21], we use ScanSAR data in X-band provided by the TerraSAR-X satellite (for technical specifications, see Table I). The shorter wavelength of the Xband signal yields a slightly different radar response compared with C-band (as delivered by RADARSAT or Sentinel) and reportedly much different response compared with L-band data [22]. This is mostly due to a much higher penetration depth of EM rays at L-band than at C-band or X-band.…”
Section: Introductionmentioning
confidence: 96%
“…While most of the work carried out in the past was concerned with C-band data; confer, e.g., [7]- [21], we use ScanSAR data in X-band provided by the TerraSAR-X satellite (for technical specifications, see Table I). The shorter wavelength of the Xband signal yields a slightly different radar response compared with C-band (as delivered by RADARSAT or Sentinel) and reportedly much different response compared with L-band data [22]. This is mostly due to a much higher penetration depth of EM rays at L-band than at C-band or X-band.…”
Section: Introductionmentioning
confidence: 96%
“…RI-1 has higher NESZ than RS-2, which could, in general, be a disadvantage for identifying sea ice types with low backscattering, e.g., grease ice. RI-1, however, has spatially finer resolution than RS-2, which might be an advantage in identifying more detailed sea ice structure like narrow ridges and rafting patterns [15]. Table 1.…”
Section: Sensor Properties and The Sar Scenesmentioning
confidence: 99%
“…X band is found to have good separation capabilities between first-year ice and old ice , between water and sea ice (Brath et al, 2013) and in detection of thin ice (Matsuoka et al, 2001). Results from the Baltic Sea suggest that the information content in C and X band are largely equivalent (Mäkynen and Hallikainen, 2004;Eriksson et al, 2010), while X band was found to add information when used in combination with C band in the Arctic Ocean (Brath et al, 2013).…”
Section: A S Fors Et Al: Late-summer Sea Ice Segmentation With Mulmentioning
confidence: 96%